Bacillus sp. VK2 ISOLATED FROM Acropora hyacinthus FROM NINH THUAN AND ITS ANTIMICROBIAL ACTIVITIES AGAINST CAUSE OF WHITE POX DISEASE IN Acropora palmate - Mien, Pham Thi; Thang, Nguyen Ngoc; Hanh, Nguyen Kim (Vietnam Journal of Marine Science and Technology, 2018)
Coral associated bacteria and their role for the host are currently one of the interested issues for research and scientists worldwide. Search of associated bacteria with some species of hard coral in Hang Rai, Ninh Thuan found that the strain VK2 was the most abundant culture from Acropora hyacinthus. This bacterium was implicated to further study for antimicrobial tests with Bacillus subtilis ATCC6633, Salmonella typhimurium ATCC6994, Escherichia coli O157, and Serratia marcescens PDL100 by agar diffusion method on MHA. The bacterium was identified as Bacillus sp. VK2. This strain showed inhibition of Serratia marcescens strain PDL100-as pandemic white pox disease for elkhorn coral Acropora palmata in Florida Keys, USA. However Bacillus sp. strain VK2 showed no inhibition against other indicators.